2015
DOI: 10.1371/journal.pone.0138793
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Intensity Interval Training and Strength Training on Metabolic, Cardiovascular and Hormonal Outcomes in Women with Polycystic Ovary Syndrome: A Pilot Study

Abstract: BackgroundPolycystic ovary syndrome is a common endocrinopathy in reproductive-age women, and associates with insulin resistance. Exercise is advocated in this disorder, but little knowledge exists on the optimal exercise regimes. We assessed the effects of high intensity interval training and strength training on metabolic, cardiovascular, and hormonal outcomes in women with polycystic ovary syndrome.Materials and MethodsThree-arm parallel randomized controlled trial. Thirty-one women with polycystic ovary sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
248
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(262 citation statements)
references
References 45 publications
8
248
1
5
Order By: Relevance
“…When measured directly with the gold standard euglycaemic clamp, intensified exercise training improved IR by 16% in overweight and obese women with PCOS, yet in BMI matched non-PCOS controls a 23% improvement was noted, emphasizing the intrinsic IR defects of the disorder. 54 Other studies using indirect measures of IR have reported a 9-30% improvement in fasting insulin 55,56 as well as in the IR indices, HOMA-IR and AUC INS , following exercise. 55,56 All previous studies have reported improvements with 12 weeks of exercise intervention, independent of the type or frequency of exercise, with 3-5 sessions per week of both moderate (40-70% VO2 max) and higher intensity interval training (95-100% VO2 max), shown to be effective.…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
See 2 more Smart Citations
“…When measured directly with the gold standard euglycaemic clamp, intensified exercise training improved IR by 16% in overweight and obese women with PCOS, yet in BMI matched non-PCOS controls a 23% improvement was noted, emphasizing the intrinsic IR defects of the disorder. 54 Other studies using indirect measures of IR have reported a 9-30% improvement in fasting insulin 55,56 as well as in the IR indices, HOMA-IR and AUC INS , following exercise. 55,56 All previous studies have reported improvements with 12 weeks of exercise intervention, independent of the type or frequency of exercise, with 3-5 sessions per week of both moderate (40-70% VO2 max) and higher intensity interval training (95-100% VO2 max), shown to be effective.…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…54 Other studies using indirect measures of IR have reported a 9-30% improvement in fasting insulin 55,56 as well as in the IR indices, HOMA-IR and AUC INS , following exercise. 55,56 All previous studies have reported improvements with 12 weeks of exercise intervention, independent of the type or frequency of exercise, with 3-5 sessions per week of both moderate (40-70% VO2 max) and higher intensity interval training (95-100% VO2 max), shown to be effective. [54][55][56] Reported changes to BMI with exercise are 1.5kg/m 2 (-0.85 to -2.1kg/m 2 ) within three to six months of exercise.…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…24 There was also a significant improvement in body composition without reductions in the total weight of lean women, regardless of the type of training when highintensity interval aerobic physical exercise and PRT were compared. 25 These studies are pioneers in the evaluation of PRT alone, in women with PCOS, and attest that strength training can be an excellent and effective exercise option.…”
mentioning
confidence: 99%
“…Norman et al, (2007) demonstraram que a diminuição de peso induzida pela dieta e /ou exercício físico promove melhorias endócrinas, metabólicas e reprodutiva em pacientes obesas com SOP. Almenning et al, (2015) encontraram redução da resistência à insulina, bem como melhora da composição corporal em mulheres com SOP. Além disso, estes exercícios utilizam grandes grupos musculares em atividades que são de natureza rítmica ou dinâmica, ocasionando o aumento da capacidade aeróbia em longo prazo.…”
Section: Introductionunclassified